ANALISIS TERHADAP SANKSI PIDANA BAGI PELAKU KEKERASAN DALAM RUMAH TANGGA YANG MENGAKIBATKAN HILANGNYA NYAWA ORANG LAIN - Qiram, Syahrul; Taufik, Moh (LPPM Universitas Bina Bangsa, 2024)
Nowadays, we encounter many criminal acts of domestic violence, and it is not uncommon for others to lose their lives. As an effort by the government to solve this problem is by socialization, Law Number 23 of 2004 concerning the Elimination of Domestic Violence (KDRT)